Paraneoplastic syndromes in dermatology - cutaneous manifestations of internal malignancy - Matyja, Karolina; Berner, Aleksandra; Stencel, Katarzyna; Pękała, Maciej; Olszewska, Anna; Stelmaszak, Karina; Marczyk, Klaudia; Polak, Paulina; Polaszek, Monika; Bogowska, Marta (Journal of Education, Health and Sport, 2023)
Introduction: Cutaneous manifestations linked with internal malignancies can exhibit a wide range of appearances.The ideal paraneoplastic marker is one that exclusively appears with a tumor, vanishes upon tumor treatment, and can potentially reemerge with tumor recurrence or metastasis. They are divided into two main categories: acquired and genetic conditions. Among acquired paraneoplastic syndromes a few are strongly correlated with internal malignancies, others have less pronounced associations. Aim of the study: To review the current literature on the topic of dermatological paraneoplastic syndromes. Materials and Methods: We reviewed the literature available in PubMed, using the key words: “paraneoplastic syndromes”, “paraneoplastic dermatoses”, “paraneoplastic syndromes in dermatology”. Results: We presented the most common, selected skin paraneoplastic syndromes. We indicated the types of neoplasms associated with these dermatoses and described their clinical appearance along with potential mechanisms of development. Summary: Timely recognition of paraneoplastic skin manifestations is crucial as they can provide an opportunity for diagnosing and treating the underlying neoplasm. That’s why dermatologists and clinicians should be familiar with this topic to perform an early diagnosis of the underlying malignancy.